Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s13201-015-0313-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical analysis and evaluation of surface water quality of Pratapgarh district, Uttar Pradesh, India

Abstract: The hydrogeochemical study of surface water in Pratapgarh district has been carried out to assess the major ion chemistry and water quality for drinking and domestic purposes. For this purpose, twenty-five surface water samples were collected from river, ponds and canals and analysed for pH, electrical conductivity, total dissolved solids (TDS), turbidity, hardness, major cations (Ca 2? , Mg 2? , Na ? and K ? ), major anions (HCO 3 -, F -, Cl -, NO 3 -, SO 4 2-) and dissolved silica concentration. The analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(59 citation statements)
references
References 31 publications
1
58
0
Order By: Relevance
“…The turbidity is one of the important physical parameters for water quality, defining the presence of suspended solids in water and causes the muddy or turbid appearance of water body (Tiwari et al 2015). In the present study area, the turbidity was found varied between the borehole and spring water sources (Fig.…”
Section: Turbiditymentioning
confidence: 69%
See 1 more Smart Citation
“…The turbidity is one of the important physical parameters for water quality, defining the presence of suspended solids in water and causes the muddy or turbid appearance of water body (Tiwari et al 2015). In the present study area, the turbidity was found varied between the borehole and spring water sources (Fig.…”
Section: Turbiditymentioning
confidence: 69%
“…The general increase of pH in a sedimentary terrain is related to weathering of plagioclase feldspar in sediments. This is aided by dissolved atmospheric carbon dioxide resulting in the release of sodium and calcium, which progressively increases pH and alkalinity of the groundwater (Venkatramanan et al 2013). The water from the borehole groundwater sources can also easily corrode the water piping due to the acidic nature of the water.…”
Section: Spatial Variations In the Physico-chemical Characteristics Omentioning
confidence: 99%
“…Water quality was also studied in different areas of the world by Dhamodharan et al (2016) [10], Li et al (2016) [11], Nagaraju et al (2016) [12], Kumar et al (2017) [13], and Tiwari et al (2017) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, WQI can be used as a powerful tool to get overall information and a comprehensive summary of environmental performance on water quality in a readily explicit form that can be utilized by administrators, decision makers and people in an understandable pattern [7]. Further, WQI is neither a replacement to the detailed analysis of environmental monitoring and modeling, nor should it be the only tool for the management of water bodies.…”
Section: Introductionmentioning
confidence: 99%